Insights into the Mechanism of a Covalently Linked Organic Dye–Cobaloxime Catalyst System for Dye‐Sensitized Solar Fuel Devices. Issue 11 (3rd May 2017) - Pati, Palas Baran; Zhang, Lei; Philippe, Bertrand; Fernández‐Terán, Ricardo; Ahmadi, Sareh; Tian, Lei; Rensmo, Håkan; Hammarström, Leif; Tian, Haining
Abstract: A covalently linked organic dye–cobaloxime catalyst system based on mesoporous NiO is synthesized by a facile click reaction for mechanistic studies and application in a dye‐sensitized solar fuel device. The system is systematically investigated by photoelectrochemical measurements, density functional theory, time‐resolved fluorescence, transient absorption spectroscopy, and photoelectron spectroscopy. The results show that irradiation of the dye–catalyst on NiO leads to ultrafast hole injection into NiO from the excited dye, followed by a fast electron transfer process to reduce the catalyst. Moreover, the dye adopts different structures with different excited state energies, and excitation energy transfer occurs between neighboring molecules on the semiconductor surface. The photoelectrochemical experiments also show hydrogen production by this system. The axial chloride ligands of the catalyst are released during photocatalysis to create the active sites for proton reduction. A working mechanism of the dye–catalyst system on the photocathode is proposed on the basis of this study. Abstract : A catalyst that wants to dye ! An organic dye–cobaloxime catalyst system based on mesoporous NiO is prepared by a facile click reaction for use in a dye‐sensitized solar fuel device. The dye–catalyst system is systematically investigated and a working mechanism on the photocathode is proposed.